Aspek Perancangan Sistem Penerangan Cerdas Berbasis Rf Transceiver - Prasetyo, Sugeng; Yasri, Indra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This paper offers ideas for designed a lighting system based RF Transceiver. design involves two sensors, sensor based infrared and sensor based light intensity and then becomes the input for the processor media. the output of the system is automatic switch lights. The automatic switch ensures that the circuit remains turned off when natural illumination is available. The automatic light is made functional from dusk to dawn because sensor reads the light intensity. A movement sensor is used to enhance the conservation of energy. It makes the automatic light operate on low brightnesswhen there is no movement. When a person is approaching, the brightness increases till the person has passed. This function is useful to indoors where it can increase power savings when there is not much movement at night.Keywords : RF Transceiver, Infrared Sensor, Light Intensity Sensor, Power Savings